TEORI EMPIRISME JOHN LOCKE DAN RELEVANSINYA TERHADAP PENDIDIKAN DASAR ISLAM - Luq Yana Chaerunnisa; Arifi (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2022)
Education for humans is an effort made to form their identity. In the process there is an educator who must be able to carry out his duties to provide competent learning. Experience and functioning of all the senses is an effective learning process. This literature review seeks to understand how the concept of John Locke's empiricism and its relevance to Islamic basic education. The method of data collection is using the documentation method. Collecting data and information from literature from various sources such as books, research results, notes, transcripts, magazines, newspapers, articles, essays, and so on.